Carbon supported Ru clusters prepared by pyrolysis of Ru precursor-impregnated biopolymer fibers. Issue 42 (19th August 2015) - Kalytta-Mewes, Andreas; Spirkl, Sebastian; Tränkle, Sebastian; Hambach, Manuel; Volkmer, Dirk
Abstract : Ru clusters deposited on pyrolyzed bacterial nanocellulose (Ru/p-BNC) were prepared in a single step by controlled pyrolysis at 1250 °C (under Ar gas), starting from bacterial nanocellulose (BNC) fibers impregnated with [RuCl2 (DMSO)4 ], which serves as a Ru precursor. Abstract : Ru clusters deposited on pyrolyzed bacterial nanocellulose (Ru/p-BNC) were prepared in a single step by controlled pyrolysis at 1250 °C (under Ar gas), starting from bacterial nanocellulose (BNC) fibers impregnated with [RuCl2 (DMSO)4 ], which serves as a Ru precursor. Pyrolyzed BNC fibers, featuring a high specific surface area (>600 m 2 g −1 ), are structurally and chemically robust supports for Ru nanoparticles, as demonstrated by temperature programmed pulse chemisorption experiments. The carbon fibers, as well as the carbon supported Ru clusters, were characterized by a range of complementary analytical techniques including high-resolution transmission electron microscopy (HRTEM), selected area electron diffraction (SAED) and Raman spectroscopy.